Mobile network forensics emerging research and opportunities - Sharevski, Filipo 1985 (Advance in Digital Crime, Forensics, and Cyber Terrorism (ADCFCT) Book Series, 2019)
"This book covers the all the aspects of conducting investigations in all generations of mobile networks with an emphasis of the current LTE deployments and future 5G technologies. It also discusses the relevant legal framework for mobile network investigations and the probative value of the associated evidence in support of the legal theory"--